Methanococci Use the Diaminopimelate Aminotransferase (DapL) Pathway for Lysine Biosynthesis - Liu, Yuchen (American Society for Microbiology (ASM), 2010)
The pathway of lysine biosynthesis in the methanococci has not been identified previously. A variant of the diaminopimelic acid (DAP) pathway uses diaminopimelate aminotransferase (DapL) to catalyze the direct conversion of tetrahydrodipicolinate (THDPA) to ll-DAP. Recently, the enzyme DapL (MTH52) was identified in Methanothermobacter thermautotrophicus and shown to belong to the DapL1 group. Although the Methanococcus maripaludis genome lacks a gene that can be unambiguously assigned a DapL function based on sequence similarity, the open reading frame MMP1527 product shares 30% amino acid sequence identity with MTH52. A Δmmp1527 deletion mutant was constructed and found to be a lysine auxotroph, suggesting that this DapL homolog in methanococci is required for lysine biosynthesis. In cell extracts of the M. maripaludis wild-type strain, the specific activity of DapL using ll-DAP and α-ketoglutarate as substrates was 24.3 ± 2.0 nmol min(−1) mg of protein(−1). The gene encoding the DapL homolog in Methanocaldococcus jannaschii (MJ1391) was cloned and expressed in Escherichia coli, and the protein was purified. The maximum activity of MJ1391 was observed at 70°C and pH 8.0 to 9.0. The apparent K(m)s of MJ1391 for ll-DAP and α-ketoglutarate were 82.8 ± 10 μM and 0.42 ± 0.02 mM, respectively. MJ1391 was not able to use succinyl-DAP or acetyl-DAP as a substrate. Phylogenetic analyses suggested that two lateral gene transfers occurred in the DapL genes, one from the archaea to the bacteria in the DapL2 group and one from the bacteria to the archaea in the DapL1 group. These results demonstrated that the DapL pathway is present in marine methanogens belonging to the Methanococcales.